Protein folding Inside the cell: macromolecular crowding and protein aggregation - Ellis, R. John (Henry Stewart Talks, 2007)
The principle of protein self-assembly, Discovery of proteins binding to newly synthesized polypeptides, Discovery of the chaperonins, Origins of the molecular chaperone concept, Replacement of spontaneous self-assembly by assisted self-assembly, Protein aggregation as a universal cellular problem, Macromolecular crowding and its effects on reaction rates and association constants, Stimulation of aggregation by crowding, How chaperones combat aggregation, Definition of molecular chaperones, The chaperone function